Ciudadanos : la Republica os llama al frente o al trabajo. Que no haya hombres inactivos (Spain. Ministerio de Instrucción Pública. Dirección General de Bellas Artes)
Red, black and white lithograph; man standing, watching as others march and work Printed by the Associación de Obreros Litógrafos, Lit. Fernandez (U.G.T.) Suggested translation: Citizens : the Republic calls you to the front, or to work! Let there be no inactive men! PO-0110